Psychological Impact of Adolescent Pregnancy in Developing Countries: A Scoping Review - Moniz, Maria de Fatima; Astuti, Andari Wuri; Hakimi, Mohammad (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: The increasing prevalence of adolescent pregnancy is a concern, as it affects 17% of the world’s population. Adolescent pregnancy could potentially have significant psychological impacts, including shameful, fearness, depression, and even suicidal thoughts. Purpose: The aim of this scoping review was to analyze the psychological effects of adolescent pregnancy in developing countries based on evidences published previously. Method: This scoping review was using Arksey and O’Malley’s approach. PEOS framework was used for identifying review question. The literature search was conducted by using three primary databases: PubMed, ScienceDirect, and Wiley Online Library. Gray literature was searched through Google Scholar, and included evidences were critically appraised by using JBI and MMAT critical appraisal tools. Results: Based on the search results of 542 articles, 7 were selected. This review focuses on the psychological impact of teenage marriage, including depression, stress, low self-efficacy in becoming parents, stigma or social pressure, and uncertainty about the future. Adolescent pregnancy leading to a negative impact on mental health, depression, stress, and low self-confidence among prospective parents. These issues arise due to a lack of psychological readiness to face the challenges of marriage, lack of family support, marital conflict, community stigmatization, ostracism, and shame. Conclusion: Adolescent pregnancy has adverse psychological impact for mother, thus it is necessary to initiate cross-sectoral work collaboration to provide health and social services as well as reducing stigma within family, peer, and community environment.